Making simple automata - Race, Robert (Ramsbury, Marlborough, Wiltshire [England] : Crowood Press Ltd, 2014)
This book explains how to design and construct small scale, simple mechanical devices made for fun. It covers materials, including paper and card, wood, wire, tinplate and plastics, and mechanisms such as levers and linkages, cranks and cams, wheels, gears, pulleys, springs, ratchets and pawls.--From back cover
Making automata -- Materials -- Mechanisms -- Magic -- Three projects -- Useful stuff and where to find it
Includes bibliographical references (pages 94-95) and index
Keywords: Toy making; Mechanical toys